Traditional Market Building Design Strategy in Post-Pandemic Era: Perspective from The Ageing Society - Wardhani, Mustika Kusumaning; Saefulloh, Asep; Muladica, Nur; Suhendar, Abyan Akmal (Prodi Arsitektur Universitas Matana, 2025)
This research examines post-pandemic strategies for designing traditional market buildings in Indonesia to accommodate the needs of older adult. The pandemic has impacted their physical and mental vulnerabilities, necessitating increased inclusive design standards. Previous research has not captured the importance of older adult preferences for post-pandemic design strategies, especially in local market buildings in Java. This research aims to provide an overview of how traditional market building designs can accommodate their preferences. This research used mixed methods, starting with a survey of 121 respondents aged 50 years and over, followed by in-depth interviews with 20 participants. Quantitative data highlights design gaps, such as a lack of greenery, inadequate parking and circulation space, and limited senior-friendly features, such as non-slip floors, seating, and ramps. The interview further detailed the older adult's needs and preferences, such as material selection, seating distribution, minimizing stairs, adding ramps and handrails, and circulation. The findings show that the current design is not sufficient to meet post-pandemic and older adult’s needs. The provision of building interior cleanliness meets minimum standards, but inclusivity is still neglected, with more than 83% of respondents stating that the design is not responsive to them. Moreover, participants emphasized the importance of reorganizing the spatial layout, including widening paths, seating for resting (or waiting), and zoning for certain commodities. The research contribution is to provide recommendations for post-pandemic traditional market designs that are responsive to the needs of the older adult. Findings advocate for traditional market spaces that are resilient and inclusive, prioritizing health and community.